Is elongated styloid process a potential forewarning for failure in oral submucous fibrosis management? - Patel, Shital Mayank; Mehta, Deval Shailesh; Rupawala, Taher Abbas; Shah, Naiya Hitesh; Makwana, Sanjay Vinubhai; Bhimani, Kruna Kantibhai (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Oral submucous fibrosis is a widespread, premalignant disorder causing severe difficulty in mastication and speech. With high rate of malignant conversion, it demands aggressive surgical therapy followed by mandatory long-term physiotherapy. An elongated styloid process, if present, could pose a strong hindrance to movement of mandible, leading to complete relapse of trismus in such cases. The purpose of this report is to elaborate on such co-existence in patients having oral submucous fibrosis using digital orthopantomogram. 3 patients suspected to have an elongated styloid process were referred to maxillofacial surgical unit and diagnosed with grade 4A oral submucous fibrosis. Digital orthopantomogram revealed elongated styloid process which was measured using the C. S. imaging software 7.0.3. Consequently, patients were operated by a team of maxillofacial surgeons and otolaryngologists to relieve trismus and tonsillo-styloidectomy respectively. The measured lengths of the styloid process on digital orthopantomogram were considered elongated, if exceeding the normal length of 30 mm. The measured lengths of the styloid process were found to be at 52.7 mm, 50.1 mm and 57 mm on the right side and 51 mm, 46.8 mm and 37 mm on left side respectively in our cases. These elongated styloid processes observed in all three cases of submucous fibrosis indicates that progressive fibrosis may exert significant influence on the ossification of styloid complex. Hence, a routine preoperative screening in all patients of oral submucous fibrosis is imminent to avoid postoperative failure, pain or discomfort to the patient owing to an elongated styloid process.